Gender Differences in Verbal Abuse and Argument Strategies in Movies: Perbedaan Gender dalam Kekerasan Verbal dan Strategi Perdebatan dalam Film - Kadhim, Hanan Abdalkareem; Kareem , Maram Salam Abdul; Kareem , Nahid Raoof (Indonesian Journal on Health Science and Medicine, 2025)
Background: Language serves as both a communicative tool and a means of exercising social power. In cinematic dialogues, verbal abuse and normal arguments often reflect deeper gendered communicative practices. Specific Background: While many studies focus on impoliteness or politeness theories separately, few have comparatively analyzed male and female speech in film discourse. Knowledge Gap: Limited research investigates how gender influences the use of verbal abuse strategies and speech acts in both aggressive and normal arguments within movies. Aim: This study examines linguistic differences between men and women in two films, Revolutionary Road and My Fault, by applying Evans’ verbal abuse model, Searle’s speech act theory, Brown and Levinson’s politeness theory, and Culpeper’s impoliteness framework. Results: Findings indicate that men predominantly employ name-calling and abusive anger with positive and negative impoliteness, whereas women frequently use judging and criticizing through bald on record and positive impoliteness. In normal arguments, men favor representative speech acts with negative politeness, while women rely on directive speech acts with bald on record politeness. Novelty: This comparative study integrates multiple pragmatic models to reveal systematic gendered patterns in cinematic communication. Implications: The results highlight how film dialogue reproduces gendered linguistic behavior, offering insights for discourse studies, gender linguistics, and media analysis. Highlights: Men use name-calling and abusive anger more. Women rely on judging and criticizing. Gendered patterns appear in both abuse and normal arguments. Keywords: Verbal Abuse, Gender Differences, Politeness, Speech Acts, Impoliteness